Bilgiyi Süzmek - M. Tayfun Gülle (Türk Kütüphaneciliği)
The article deals with the concerns about Secure Internet Law to be enforced on November 22, 2011, and points out that individuals of democratic societies are capable of filtering information and families have a part to play in protecting from the information pollution on the Internet. In connection with this, “Statement on Library Use of Filtering Software” by American Library Association is introduced.